1991
DOI: 10.1093/jnci/83.20.1483
|View full text |Cite
|
Sign up to set email alerts
|

Her-2/neu and INT2 Proto-oncogene Amplification in Malignant Breast Tumors in Relation to Reproductive Factors and Exposure to Exogenous Hormones

Abstract: In previous studies in southern Sweden, early use of oral contraceptives has been found to be accompanied by an increased risk of developing premenopausal breast cancer, and the tumors developing in these patients have shown a more aggressive behavior. In the present study, amplification of the proto-oncogenes Her-2/neu (also known as ERBB2) and INT2 was studied in primary tumor specimens from 72 premenopausal women and was related to starting age of oral contraceptive use and other reproductive risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
2
13
3
Order By: Relevance
“…However, the variables investigated here have not previously been shown to affect survival, but several have been shown to affect incidence in previous studies of breast cancer; therefore, any apparent risk factors found here likely reflect these variables' effect on incidence rather than on survival. One possible exception is for OCs, which have recently been associated with a somatic mutation of the Her-2 oncogene that is associated with poorer prognosis [10]. If this association is real and strong, it may have caused a conservative bias (towards the null) for the OC effect in our data.…”
Section: Discussionmentioning
confidence: 76%
“…However, the variables investigated here have not previously been shown to affect survival, but several have been shown to affect incidence in previous studies of breast cancer; therefore, any apparent risk factors found here likely reflect these variables' effect on incidence rather than on survival. One possible exception is for OCs, which have recently been associated with a somatic mutation of the Her-2 oncogene that is associated with poorer prognosis [10]. If this association is real and strong, it may have caused a conservative bias (towards the null) for the OC effect in our data.…”
Section: Discussionmentioning
confidence: 76%
“…Cyclin D1 expression has been correlated with ER levels in breast cancer, suggesting that ER is a key regulator of cyclin D1 expression in primary breast tumors [22,23]. In addition, amplification of the cyclin D1 gene occurs almost invariably in ER-positive breast cancer, suggesting that ER and cyclin D1 cooperate in driving tumor growth [23][24][25]. Furthermore, overexpression or amplification of cyclin D1 has been shown to predict early relapse and poor prognosis in ER-positive tumors [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with various studies where HER-2/neu or its protein P185 is over-expressed in 10-35% of breast cancer patients in the western population an over amplification of this gene in 25-30%, have been reported. [8][9][10] Age at presentation…”
Section: Discussionmentioning
confidence: 99%